Analysis of Optimal Portfolio Comparison on Shares of Sri Kehati by using Single Index Model and Random Model - Rollis Ayu Ditasari; Ade Ichsan Pradana (Publisher Cv. Inara, 2021)
The purpose of this study is to provide empirical evidence that the determination of a stock portfolio using a single index model can provide optimal returns compared with the determination of stock portfolio using a random model. The sample in this research is 25 shares joined in SRI-KEHATI selected using purposive sampling. The data analysis technique used the average test for two independent samples (Mann Whitney Test (U Test)). The results showed that the determination of the stock portfolio using a single index model can provide optimal return compared to the determination of the stock portfolio using random model.